Phase Transitions in Pure and Hybrid Hydrogels: A Fluorescence Study - Aktas, Demet Kaya; Evingür, Gülşen Akin; Pekcan, Önder (Wiley, 2009)
AbstractSummary: Recent observations on phase transitions around the critical point showed that the critical exponents differed drastically from percolation results and classical results for pure hydrogel systems, depending on monomer concentration. In addition to pure hydrogels, the sol‐gel phase transition during radical crosslinking copolymerization of acrylamide (AAm) and N‐isopropylacrylamide (NIPA) hybrid was studied by using the steady state fluorescence (SSF) technique. N,N′‐methylenebis(acrylamide) (BIS) and ammonium persulfate (APS) were used as crosslinker and initiator, respectively. Pyranine (trisodium 8‐hydroxypyrene‐1,3,6‐trisulfonate acid, HPTS) was added as a fluoroprobe for monitoring the polymerization. It was observed that pyranine binds to AAm and NIPA chains on the initiation of the polymerization, thus the fluorescence spectra of the bonded pyranines shift to shorter wavelengths. Fluorescence spectra of the bonded pyranines allowed to monitor the sol‐gel phase transition without disturbing the system mechanically and to test the universality of the sol‐gel transition as a function of polymer concentration ratios. The observations around the gel point of PAAm‐PNIPA hybrid show that the gel fraction exponent β obeyed the percolation result.
Keywords: Percolation; Hydrogels; Fluorescence; Hybrid; Critical phenomena